ANALISIS GAYA BAHASA PENGANTAR GURU DALAM PROSES PEMBELAJARAN SISWA KELAS VI SDI BONTOBILA: ANALYSIS OF TEACHER'S INTRODUCTORY LANGUAGE STYLE IN THE LEARNING PROCESS OF CLASS VI STUDENTS AT SDI BONTOBILA - Aulia, Magfirah; Ramly; Idawati (Journal of Applied Linguistics and Literature, 2023)
This research aims to describe the intensity of Indonesian as the teacher's language of instruction in developing the speaking skills of class VI students at SD Inpres Bontobila, describing the problems of using the teacher's language of instruction in communicating with students in the classroom. This type of research is qualitative. The research results revealed that the intensity of using Indonesian as the language of instruction in the learning process was limited to simple basic sentences regarding standard learning requirements, both in initial activities, core activities, and final learning activities. The problems of using the teacher's language of instruction in communicating with students in the classroom are classified into three problems: the use of standard Indonesian, which hinders learning; differences in the rules of regional languages and Indonesian, causing language interference; and the frequent use of regional languages in educational environments and learning situations.